2020
DOI: 10.1101/2020.02.03.931931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging mass spectrometry and shotgun proteomics reveal dysregulated pathways in hormone induced male infertility

Abstract: ABBREVIATIONS MALDI-IMS -Matrix assisted laser desorption/ionisation imaging mass spectrometry LC-MS -Liquid chromatography mass spectrometry WT -Wild type AROM+ -Mice overexpressing human P450 aromatase E2/T -Estrogen/Testosterone ratio ECM -Extracellular matrix ER -Endoplasmic reticulum GO -Gene ontology UPR -Unfolded protein response AbstractSpermatogenesis is a complex multi-step process involving intricate interactions between different cell types in the male testis. Disruption of these interactions resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For chickpea sections, two different washing protocols were tested: The first, according to Grassl et al, includes two washing steps for 30 s with 70% ice-cold 2-propanol and a 15 s step with 95% ice-cold 2-propanol. The second was modified from Enthaler et al, using two cycles of 70 and 100% ice-cold ethanol for 30 s each, with 5 dips in ammonium bicarbonate buffer at pH 4.5 in between . The buffer was introduced instead of pure water for better protein fixation due to the isoelectric point of most chickpea proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For chickpea sections, two different washing protocols were tested: The first, according to Grassl et al, includes two washing steps for 30 s with 70% ice-cold 2-propanol and a 15 s step with 95% ice-cold 2-propanol. The second was modified from Enthaler et al, using two cycles of 70 and 100% ice-cold ethanol for 30 s each, with 5 dips in ammonium bicarbonate buffer at pH 4.5 in between . The buffer was introduced instead of pure water for better protein fixation due to the isoelectric point of most chickpea proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The second was modified from Enthaler et al, 46 using two cycles of 70 and 100% ice-cold ethanol for 30 s each, with 5 dips in ammonium bicarbonate buffer at pH 4.5 in between. 47 The buffer was introduced instead of pure water for better protein fixation due to the isoelectric point of most chickpea proteins. The comparison showed that with the latter protocol, some proteins are washed off the section, and the corresponding tryptic peptides could not be detected, as demonstrated for tryptic peptides of 40S ribosomal protein S4 (Accession No.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study [ 3 ], proteomes from both WT and AROM + testes of 11 month-old animals ( n = 3, each) were studied by mass spectrometry and the datasets were screened for macrophage markers, inflammation markers, TRPV2 and ROS generating enzymes ( Figure 3 ). The macrophage markers CAPG, CD68, and CD206 were readily found in all three animals of both genotypes with the mean iBAQ intensities being significantly higher in testes from AROM animals (CAPG: p = 0.0097; CD68: p = 0.0484; CD206: p = 0.0007).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic mice overexpressing aromatase (AROM + ) have been studied for many years [ 1 , 2 , 3 ]. The hormonal imbalance in these animals causes immunological changes and, in some organs, inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…the integration of molecular (DNA, RNA, protein) data and lineage data, possibly with three-dimensional spatial resolution (or even fourdimensional, temporal resolution). Indeed, more and more single cell sequencing studies are already being published (125,126) and together with other approaches (127,128), they eventually will provide a clear and precise picture of the sources of biogenic amines, and their testicular receptors, as well as their changes during development, aging and diseases.…”
Section: Discussionmentioning
confidence: 99%